Decolonizing Indigenous science: Bees and Indigenous sovereignty - Phoenix Nakagawa; Hanika Nakagawa; Kyle Bobiwash (FACETS)
In this conceptual paper, we argue that the assumptions behind laboratory and field studies are that chemical and compositional analysis may reveal structures unseen by means of human observation. However, replacing human observation to make it obsolete is not the purpose of science; if something can be seen, but is not measurable, that does not make it irrelevant. Although science is frequently primarily regarded as a quantitative field, we argue that qualitative data inclusion is necessary determine the consequences of research on Indigenous communities. We discuss key points, including historical and anthropocentric views of science, suggesting that Indigenous Science requires greater wisdom-based knowledge in association with traditional ecological knowledge. We introduce a new conceptual model called “Pollen Sovereignty”, a sister to Indigenous food sovereignty, to begin critical discussions around the ethics of field research and the impacts of research on the environment, land management, and Indigenous communities. That is, through simple scientific concepts, critical thought, and logic new conceptual frameworks and avenues of research, Indigenous knowledges cannot merely be coopted and reused, but respected and valued.